Antidepressants and benzodiazepines for panic disorder in adults - Bighelli, Irene (Cochrane Database Syst Rev, 2016)
BACKGROUND: A panic attack is a discrete period of fear or anxiety that has a rapid onset, reaches a peak within 10 minutes and in which at least four of 13 characteristic symptoms are experienced, including racing heart, chest pain, sweating, shaking, dizziness, flushing, stomach churning, faintness and breathlessness. Panic disorder is common in the general population with a lifetime prevalence of 1% to 4%. The treatment of panic disorder includes psychological and pharmacological interventions. Amongst pharmacological agents, antidepressants and benzodiazepines are the mainstay of treatment for panic disorder. Different classes of antidepressants have been compared; and the British Association for Psychopharmacology, and National Institute for Health and Care Excellence (NICE) consider antidepressants (mainly selective serotonin reuptake inhibitors (SSRIs)) as the first‐line treatment for panic disorder, due to their more favourable adverse effect profile over monoamine oxidase inhibitors (MAOIs) and tricyclic antidepressants (TCAs). In addition to antidepressants, benzodiazepines are widely prescribed for the treatment of panic disorder. OBJECTIVES: To assess the evidence for the effects of antidepressants and benzodiazepines for panic disorder in adults. SEARCH METHODS: The Specialised Register of the Cochrane Common Mental Disorders Group (CCMDCTR) to 11 September 2015. This register includes relevant randomised controlled trials from the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE (1950‐), Embase (1974‐) and PsycINFO (1967‐). Reference lists of relevant papers and previous systematic reviews were handsearched. We contacted experts in this field for supplemental data. SELECTION CRITERIA: All double‐blind randomised controlled trials allocating adult patients with panic disorder to antidepressants or benzodiazepines versus any other active treatment with antidepressants or benzodiazepines. DATA COLLECTION AND ANALYSIS: Two review authors independently checked eligibility and extracted data using a standard form. Data were entered in RevMan 5.3 using a double‐check procedure. Information extracted included study characteristics, participant characteristics, intervention details, settings and outcome measures in terms of efficacy, acceptability and tolerability. MAIN RESULTS: Thirty‐five studies, including 6785 participants overall (of which 5365 in the arms of interest (antidepressant and benzodiazepines as monotherapy)) were included in this review; however, since studies addressed many different comparisons, only a few trials provided data for primary outcomes. We found low‐quality evidence suggesting no difference between antidepressants and benzodiazepines in terms of response rate (risk ratio (RR) 0.99, 95% confidence interval (CI) 0.67 to 1.47; participants = 215; studies = 2). Very low‐quality evidence suggested a benefit for benzodiazepines compared to antidepressants in terms of dropouts due to any cause, even if confidence interval (CI) ranges from almost no difference to benefit with benzodiazepines (RR 1.64, 95% CI 1.03 to 2.63; participants = 1449; studies = 7). We found some evidence suggesting that serotonin reuptake inhibitors (SSRIs) are better tolerated than TCAs (when looking at the number of patients experiencing adverse effects). We failed to find clinically significant differences between individual benzodiazepines. The majority of studies did not report details on random sequence generation and allocation concealment; similarly, no details were provided about strategies to ensure blinding. The study protocol was not available for almost all studies so it is difficult to make a judgment on the possibility of outcome reporting bias. Information on adverse effects was very limited. AUTHORS' CONCLUSIONS: The identified studies are not sufficient to comprehensively address the objectives of the present review. The majority of studies enrolled a small number of participants and did not provide data for all the outcomes specified in the protocol. For these reasons most of the analyses were underpowered and this limits the overall completeness of evidence. In general, based on the results of the current review, the possible role of antidepressants and benzodiazepines should be assessed by the clinician on an individual basis. The choice of which antidepressant and/or benzodiazepine is prescribed can not be made on the basis of this review only, and should be based on evidence of antidepressants and benzodiazepines efficacy and tolerability, including data from placebo‐controlled studies, as a whole. Data on long‐term tolerability issues associated with antidepressants and benzodiazepines exposure should also be carefully considered. The present review highlights the need for further higher‐quality studies comparing antidepressants with benzodiazepines, which should be conducted with high‐methodological standards and including pragmatic outcome measures to provide clinicians with useful and practical data. Data from the present review will be included in a network meta‐analysis of psychopharmacological treatment in panic disorder, which will hopefully provide further useful information on this issue.